Achieving gender equality by implementing work–life balance measures in Swiss SMEs. Issue 4 (2nd October 2022) - Burkhard, Danielle
ABSTRACT: Key points identified in this study to break through the glass ceiling and reach not only gender parity, but also a work–life balance from which all employees can equally benefit, are: improve girls' position early on at school, give women sponsors and mentors to help them develop the competencies to be confident, offer parental leave to encourage women to come back after giving birth, implement new work forms, give employees the possibility for care work, and put legal and political regulations as well as policies in place to influence companies' decisions when implementing new measures. To introduce new measures into a company's organizational structure, a detailed research process on which measures are requested and can be implemented, as well as an external consultant or tool, need to be used. This process is very individual per company. The goal is to improve employee satisfaction, have less fluctuations, and put extra financial costs into perspective.